Hamilton babylon : a history of the McMaster Film Board - Broomer, Stephen (Toronto ; Buffalo ; London : University of Toronto Press, 2015)
Founded in 1966 at McMaster University by avant-garde filmmaker John Hofsess and future frat-comedy innovator Ivan Reitman, the McMaster Film Board was a milestone in the development of Canada's commercial and experimental film communities. McMaster's student film society quickly became the site of art filmmaking and an incubator for some of the country's most famous commercial talent - as the well as the birthplace of the first Canadian film to lead to obscenity charges, Hofsess's Columbus of Sex. In Hamilton Babylon, Stephen Broomer traces the history of the MFB from its birth as an organization for producing and exhibiting avant-garde films, through its transformation into a commercial-industrial enterprise, and into its final decline as a show business management style suppressed many of its voices. The first book to highlight the work of Hofsess, an innovative filmmaker whose critical role in the MFB has been almost entirely eclipsed by Reitman's legend, Hamilton Babylon is a fascinating study of the tension between art and business in the growth of the Canadian film industry.
Frontmatter -- Contents -- Illustrations -- Acknowledgments -- Hamilton Babylon A History Of The Mcmaster Film Board -- Introduction -- CHAPTER ONE. A Dangerous Precedent -- CHAPTER TWO. Assembling Pleasure -- CHAPTER THREE. A New President -- CHAPTER FOUR. Participatory Democracy -- CHAPTER FIVE. Seize The Projectors -- CHAPTER SIX. Sync Sound Arrives -- CHAPTER SEVEN. The Film Board Presidents On Trial -- CHAPTER EIGHT. The Appeal -- CHAPTER NINE. Show Business -- Appendix: Mcmaster Film Board Filmography -- Notes -- Bibliography -- Index
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: McMaster Film Board; McMaster Film Board; Motion pictures -- Production and direction -- Ontario -- Hamilton -- History; Motion pictures -- Ontario -- Hamilton -- History; Motion pictures, Canadian -- Ontario -- Hamilton -- History; Experimental films -- Ontario -- Hamilton -- History and criticism; Motion picture producers and directors -- Ontario; Cinéma -- Production et réalisation -- Ontario -- Hamilton -- Histoire; Cinéma -- Ontario -- Hamilton -- Histoire; Cinéma canadien -- Ontario -- Hamilton -- Histoire; Producteurs et réalisateurs de cinéma -- Ontario; PERFORMING ARTS -- Reference; ART -- General; Experimental films; Motion picture producers and directors; Motion pictures; Motion pictures, Canadian; Motion pictures -- Production and direction; Ontario; Ontario -- Hamilton; Criticism, interpretation, etc; History